The Role of Intrusive Thoughts and Self-Compassion in Predicting Academic Procrastination Among University Students - Atashpour , Seyed Salar; Atashpour , Samieh Sadat (Journal of Personality and Psychosomatic Research (JPPR), 2025)
The primary objective of this study was to investigate the relationships between academic procrastination, intrusive thoughts, and self-compassion among university students. This research aimed to determine whether intrusive thoughts and self-compassion can predict academic procrastination behaviors. This cross-sectional study included 302 university students selected based on the Morgan and Krejcie (1970) sample size determination table. Participants completed self-report measures, including the Academic Procrastination Scale (APS), White Bear Suppression Inventory (WBSI), and Self-Compassion Scale (SCS). Data were analyzed using Pearson correlation and linear regression analyses to examine the relationships between the variables. IBM SPSS Statistics version 27 was utilized for data analysis. The results indicated significant correlations between academic procrastination, intrusive thoughts, and self-compassion. Academic procrastination was positively correlated with intrusive thoughts (r = 0.48, p < 0.001) and negatively correlated with self-compassion (r = -0.35, p < 0.001). Regression analysis revealed that intrusive thoughts (β = 0.41, p < 0.001) and self-compassion (β = -0.29, p < 0.001) were significant predictors of academic procrastination, explaining 34% of the variance in procrastination behaviors (R² = 0.34). This study highlights the significant roles of intrusive thoughts and self-compassion in academic procrastination. Intrusive thoughts increase the likelihood of procrastination, while self-compassion acts as a protective factor, reducing procrastination tendencies. These findings suggest that interventions aimed at reducing intrusive thoughts and enhancing self-compassion may be effective in mitigating academic procrastination. Future research should explore longitudinal and intervention-based studies to further understand and address this issue.